Bentuk dan Fungsi Ungkapan Tradisional pada Film Pendek Berbahasa Jawa - Chumaidah, Dian Ayu Nurul; Fateah, Nur (Aksara: Jurnal Bahasa dan Sastra, 2025)
Language is a communication system using symbols in the form of words, sentences, and signs to convey thoughts or feelings between one human being and another. With language, Javanese people often utter figurative sentences that have a specific purpose. These figurative sentences are traditional Javanese expressions that are often used as satire, advice, ridicule, and so on. In this study, the author explains the forms and functions of traditional Javanese expressions in Javanese short films. In addition to daily face-to-face activities, traditional expressions can also be found through audio visuals such as YouTube content which of course has the intent and purpose of expressing advice, satire, reminders, and so on. This study uses Ferdinand De Saussure's semantic theory (1966). This data collection uses the free conversation listening technique. Data was obtained by listening to the content on the Paniradya Kaistimewaan YouTube channel in a short film entitled Pitutur 2, Latar, and Dalan Rejeki. This study produced seven data consisting of three forms of traditional Javanese expressions and 3 functions of traditional Javanese expressions. This study aims to reveal the preservation of culture, especially in the form of traditional Javanese expressions. It is expected from the author that readers can grow an understanding of the existence of forms and functions of traditional Javanese expressions and grow awareness of the importance of culture in community life.Keywords: Language, Traditional Expressions, Forms, Functions